Relationship between the iceA gene of Helicobacter pylori and clinical outcomes - Huang XJ; Deng ZM; Zhang Q; Li WY; Wang BN; Li MY (Dove Medical Press, 2016)
Xiaojun Huang,1,2 Zhaomin Deng,1 Qiang Zhang,1 Wanyi Li,1 Baoning Wang,1 Mingyuan Li1,3 1Department of Microbiology, West China School of Preclinical and Forensic Medicine, Sichuan University, Chengdu, People’s Republic of China; 2Department of Microbiology, School of Medicine, Hubei University for Nationalities, Enshi, People’s Republic of China; 3State Key Laboratory of Oral Diseases, Chengdu, People’s Republic of China Background: The complex pathogenesis of Helicobacter pylori (H. pylori) and the features of the host influence the diverse clinical outcomes. A mass of studies about virulence genes have accelerated the exploration of pathogenesis of H. pylori infection. Induced by contact with epithelium gene A (iceA) is one of the biggest concerned virulence genes. In this study, we explored the relationship between iceA and the magnitude of the risk for clinical outcomes and the prevalence of iceA-positive H. pylori in People’s Republic of China and other countries.Methods: We searched the electronic databases of PubMed, Embase, CNKI, VIP, and Wanfang by literature search strategy. The studies conforming to the inclusion criteria were assessed. With these data, we systematically analyzed the relationship between the iceA gene of H. pylori and clinical outcomes.Results: Nineteen articles with 22 studies, a total of 2,657 cases, were involved in the study. The iceA1 gene was significantly associated with peptic ulcer disease (odds ratio =1.28, 95% confidence interval =1.03–1.60; P=0.03), especially in People’s Republic of China (odds ratio =1.40, 95% confidence interval =1.07–1.83; P=0.01). Moreover, the prevalence of iceA1 was significantly higher than iceA2 in People’s Republic of China (P<0.0001). The prevalence of both iceA1 and iceA2 was significantly different (P<0.0001) in People’s Republic of China and in other countries.Conclusion: The system analysis showed that infection with the iceA1-positive H. pylori significantly increased the overall risk for peptic ulcer disease, especially in People’s Republic of China. The iceA2 gene status and clinical outcome of H. pylori infection have no significant correlation. H. pylori iceA1 genotype is the major epidemic strain in People’s Republic of China. Keywords: Helicobacter pylori, iceA, gastritis, peptic ulcer disease, gastric carcinoma